Critical Discourse Analysis of Celebrant Reporting in Online Media the Fairclough and Teun A Van Djik Approach Model - Hismulyati; Teguh Setiawan (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2023)
The mass media is a tool for conveying information, thoughts and ideas to a wide audience. The information conveyed varied, including news about the lives of celebrities in Indonesia. Through critical discourse analysis, it is possible to find findings about ideology contained in a report in various existing media. The purpose of this study was to find out critical discourse analysis of the news about Dara Arafah's migration published by seven online media, namely okezone.com, suara.com, hipwee.com, idmtimes.com, fimela.com, tribunnews.com, and Celebrities.id. Qualitative methods are used as a basis for thinking and a critical paradigm is used as the point of view of this research. The theory used in this study is a three-dimensional model from Norman Fairclough, namely the microstructural, mesostructural, and macrostructural. The results of this study indicate that there are differences in the content of celebrity reporting in seven online media; okezone.com, suara.com, hipwee.com, idmtimes.com, fimela.com, tribunnews.com, and Celebrities.id. Each media presents the same news topic with different framing according to the media's motivation and idealism. The results of the analysis of Teun A Van Djik's theory are Macro Structure (Themes/topics). The themes or topics in the seven reports are the migration of Dara Arafah, a beautiful celebgram who was originally famous for not covering her genitals. Even so, each news item has a different sub-theme or category. Superstructure (Schematic), Based on the scheme, each report begins with a title as a summary. The lead section describes the subject that is the reference and leads the reader to the main discourse. Micro Structure (Semantics: Setting, Detail, Purpose, Presupposition) In the seven news stories, all elements of the micro structure are found in the form of Setting, Detail, Purpose, and Presupposition. Even though they have almost the same background, namely the relation to the news about Dara Arafah's migration, each news story has its own picture regarding the background of each news. Likewise, the details, intentions, and presuppositions in each news story will vary. but each news has its own description of the background in each news. Likewise, the details, intentions, and presuppositions in each news story will vary. but each news has its own description of the background in each news. Likewise, the details, intentions, and presuppositions in each news story will vary.